Validation of the Polish version of Satisfaction with Asthma Treatment Questionnaire (SATQ) - Dońka, Katarzyna; Czarnocki, Krzysztof J.; Emeryk, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Among the chronically ill there is a tendency for non-compliance with medical recommendations, which is often due to low satisfaction with the offered treatment. Satisfaction with Asthma Treatment Questionnaire (SATQ) is a questionnaire for measuring satisfaction with the inhalation treatment of asthma in patients of more than 18 years of age. SATQ is a standardized tool that has not been previously used in Poland. SATQ consists of 4 domains: efficiency, ease of use, the burdening with asthma treatment and side effects and concerns. Aim: To validate the Polish language version of SATQ questionnaire and an overall verification of the usefulness of the tool relative to trials from clinical practice. Material and methods : The degree of difficulty and comprehension of the questions and the reliability and validity of the Polish version of the questionnaire was determined in 67 patients with asthma (mean age: 45.8 ±14.3 years (range maximum – at least 18–65 years). The vast majority of patients in the study group have used the inhalers for more than 1 year and were educated in the field of aerosols management. The resulting scores are calculated by adding up the scores for each question and dividing by the number of questions. The reliability of the questionnaire design was verified using the Spearman rank correlation coefficients between elements and ranges between band assessments and evaluations and overall assessment of quality and patient satisfaction with treatment. Internal consistency and reliability of the tool was assessed using Cronbach’s . The values of Cronbach’s α were evaluated with respect to the threshold value of 0.70. Results : SATQ questionnaire was understandable and easy to fill out for all subjects. The filling time of SATQ was designed as to be within 5–10 min. Cronbach’s α was reached on all scales, demonstrating the reliability of the analyzed scale and lack of redundancy. Conclusions : The Polish version of SATQ questionnaire meets the basic psychometric criteria and can be used to assess satisfaction with the inhalation treatment of asthma.